International survey of training load monitoring practices in competitive swimming: How, what and why not?. (January 2022) - Barry, Lorna; Lyons, Mark; McCreesh, Karen; Powell, Cormac; Comyns, Tom
Abstract: Objective: The purpose of this study is to identify the training load (TL) monitoring practices employed in real-world competitive swimming environments. The study explores data collection, analysis and barriers to TL monitoring. Design: Cross-sectional. Setting: Online survey platform. Participants: Thirty-one responders working in competitive swimming programmes. Main outcome measures: Methods of data collection, analysis, level of effectiveness and barriers associated with TL monitoring. Results: 84% of responders acknowledged using TL monitoring, with 81% of responders using a combination of both internal and external TL, in line with current consensus statements. Swim volume (mileage) (96%) and session rate of perceived exertion (sRPE) (92%) were the most frequently used, with athlete lifestyle/wellness monitoring also featuring prominently. Thematic analysis highlighted that "stakeholder engagement", "resource constraints" or "functionality and usability of the systems" were shared barriers to TL monitoring amongst responders. Conclusions: Findings show there is a research-practice gap. Future approaches to TL monitoring in competitive swimming should focus on selecting methods that allow the same TL monitoring system to be used across the whole programme, (pool-based training, dryland training and competition). Barriers associated with athlete adherence and coach/National Governing Body engagement should be addressed before a TL system implementation. Highlights: The findings show that 84% of responders participated in some level of training load monitoring. Swim volume (mileage) (96%) and sRPE (92%) were the primary data variables collected by responders. The goals of TL monitoring were primarily to "monitor athlete's response to training" or to "improve athlete performance". sRPE should be prioritised as it can be used uniformly across all aspects of a swim programme (Dryland, swim TL).